2021
DOI: 10.48550/arxiv.2102.12501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preheating from target space curvature and unitarity violation: Analysis in field space

Yohei Ema,
Ryusuke Jinno,
Kazunori Nakayama
et al.

Abstract: We study particle production and unitarity violation caused by a curved target space right after inflation. We use the inflaton field value instead of cosmic time as the time variable, and derive a semiclassical formula for the spectrum of produced particles. We then derive a simple condition for unitarity violation during preheating, which we confirm by our semiclassical method and numerical solution. This condition depends not only on the target space curvature but also on the height of the inflaton potentia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(147 reference statements)
1
1
0
Order By: Relevance
“…The same unitarity bound, U 0 Λ 4 cut , was derived in Ref. [59], although not in the context of tachyonic preheating.…”
Section: Discussionsupporting
confidence: 62%
“…The same unitarity bound, U 0 Λ 4 cut , was derived in Ref. [59], although not in the context of tachyonic preheating.…”
Section: Discussionsupporting
confidence: 62%
“…As for the preheating, it was found that the effective mass of φ becomes tachyonic after inflation [55], so that careful analyses are often necessary to estimate particle productions and resulting reheat temperature; see for example [56][57][58] and references therein.…”
Section: • α-Attractor Modelsmentioning
confidence: 99%